Analyzing of usability of tree-rings as biomonitors for monitoring heavy metal accumulation in the atmosphere in urban area: a case study of cedar tree (Cedrus sp.) - Sevik, Hakan; Cetin, Mehmet; Özel, Halil Barış; Akarsu, Hatice; Cetin, Ilknur Zeren (Springer Science and Business Media LLC, 2019)
It is important to monitor the heavy metal pollution in order to identify risk zones and to determine the change in the heavy metal concentration of the atmosphere within the process. For this, it is necessary to carry out measurements for many years; however, this is not possible. Especially from past to present, one of the most effective methods to determine the changes of heavy metal concentrations in the atmosphere is to use the annual tree rings as biomonitors. Perennial plants growing in our country create annual rings, and it is possible to gain information regarding the changes of heavy metal concentrations in that region by determining the heavy metal concentrations in these rings. In this study, it was aimed to determine the annual changes of Pb, Co, and Fe elements' concentrations in these sections by determining the annual rings on the logs taken from the main stem of the cedar tree (Cedrus sp.), which was cut by the end of 2016, in December, 2016, in Kastamonu province. Within the scope of the study, the element concentrations were also determined in the inner and outer bark. As a result of the study, it was found that the heavy metal values in the organelles taken from the road-facing part, especially the heavy metal concentrations in the outer bark were higher than the metal concentrations in the inward-facing part, and that the concentrations changed significantly on organelle and year basis.
Keywords: Atmosphere; Management, Monitoring, Policy and Law; Cedar Tree; Wood; Annual Ring; Heavy Metal; Air Pollution; Metals, Heavy; Environmental Pollution; Cedrus; Environmental Monitoring; 15. Life on land; 13. Climate action; 11. Sustainability